1973
DOI: 10.1159/000180236
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Calcitonin Therapy in Renal Osteodystrophy

Abstract: Synthetic salmon calcitonin (100 MRC units/day)was administered to three patients with chronic renal insufficiency supported by maintenance hemodialysis; these patients had also developed secondary hyperparathyroidism.The diagnosis of hyperparathyroidism was based on bone pain, X-ray changesindicating subperiosteal bone reabsorption, increased levels of serum alkaline phosphatase, accelerated radiocalcium turnover, increased resorption on bone biopsy and increased levels of bone cell collagenase activity. No i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…It seems probable that the rise in alkaline phosphatase in our patients was due to an increase in osteoblastic activity, since we and others have noted a strong positive correlation between osteoblastic surfaces and plasma alkaline phosphatase in chronic renal failure (Table 3) [14, 30, 331. The question arises whether the rise in alkaline phosphatase reflected an increase in bone turnover (increased osteoblastic bone formation plus increased bone resorption) or a net increase in bone formation (increased osteoblastic bone formation without increased bone resorption). A previous report has suggested that daily administration of salmon calcitonin in chronic renal failure may increase net bone resorption [34], but several of our observations suggest at least a transient uncoupling between the rates of bone formation and resorption. Hypocalcaemia was noted in many of the patients throughout treatment even though plasma calcium was measured 48-72 h after each dose of calcitonin.…”
Section: Iacontrasting
confidence: 68%
“…It seems probable that the rise in alkaline phosphatase in our patients was due to an increase in osteoblastic activity, since we and others have noted a strong positive correlation between osteoblastic surfaces and plasma alkaline phosphatase in chronic renal failure (Table 3) [14, 30, 331. The question arises whether the rise in alkaline phosphatase reflected an increase in bone turnover (increased osteoblastic bone formation plus increased bone resorption) or a net increase in bone formation (increased osteoblastic bone formation without increased bone resorption). A previous report has suggested that daily administration of salmon calcitonin in chronic renal failure may increase net bone resorption [34], but several of our observations suggest at least a transient uncoupling between the rates of bone formation and resorption. Hypocalcaemia was noted in many of the patients throughout treatment even though plasma calcium was measured 48-72 h after each dose of calcitonin.…”
Section: Iacontrasting
confidence: 68%
“…In a bone histomorphometric study, no correlation was found between bone activity and CT levels while correlations were observed with PTH [ 75 ]. Finally, several studies from many years ago showed that treatment with CT failed to improve renal osteodystrophy [ 76 78 ].…”
Section: Calcitonin and Renal Failurementioning
confidence: 99%